Odpowiedzi

Najlepsza Odpowiedź!
2009-12-30T19:13:16+01:00
Sprowadzam działanie do najprostszej postaci:
-12x-[4y²-7] + 5x =-12x-4y²+7+5x
Podstawiam liczby za x i y: x=-2
y=1/4
-12*(-2)-4*(1/4)²+7+5*(-2)=24-4*1/16+7-10=24-1/4-3=21-1/4=20 3/4

Pozdrawiam Kasia ;)
1 5 1
2009-12-30T20:06:58+01:00
-12*-2 -(4*(0,25)²-7)+5*-2=
=24-(4*0,0625-7)-10=
=24-(0,25-7)-10=
=24+6,75-10=
=20,75
2009-12-30T20:08:42+01:00
Jak się nie mylę to będzie tak:

-12x- [4y²-7] +5x=
-12x (-2)-[4*(1/4)² -7] + 5*(-2)=
24-4*1/16 +7-10=
21-4/16=
336/16-4/16= 20,75